2009
DOI: 10.1093/geront/gnp096
|View full text |Cite
|
Sign up to set email alerts
|

Food Avoidance and Food Modification Practices of Older Rural Adults: Association With Oral Health Status and Implications for Service Provision

Abstract: Food services for older adults should consider their oral health status. Policy changes are needed to provide oral health care in benefits for older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 36 publications
3
72
2
Order By: Relevance
“…Food avoidance measures were developed based on 10 years of research regarding the nutritional self-management of the study population (2226) and are described in detail elsewhere (12, 27). Generally the instrument consists of a list of foods commonly consumed by the population and those which represent specific eating challenges (27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food avoidance measures were developed based on 10 years of research regarding the nutritional self-management of the study population (2226) and are described in detail elsewhere (12, 27). Generally the instrument consists of a list of foods commonly consumed by the population and those which represent specific eating challenges (27).…”
Section: Methodsmentioning
confidence: 99%
“…These data have shown that older adults who avoided the greatest number of foods were more likely to have dentures, that those dentures were more likely to be ill-fitting (11) than those of persons who avoided fewer foods, and that dietary quality was lower among persons who avoided the greatest number of foods (18). This analysis considers types of removable dentures and whether or not individuals wore their dentures while eating.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors not considered here may be more related to Nutrition. For example, the type and number of medications taken, as well as oral health, can affect eating behaviors of the elderly (Pender, Murdaugh, & Parsons, 2006;Quandt et al, 2010). Also, the availability of someone who can shop and cook healthy meals may be a key factor that should be addressed in future health promotion interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Gender, age, race/ ethnicity, place of birth, education and income influence dietary quality 17 . Quandt et al 18 recently reported that among older rural adults in North Carolina, whole fruits and raw vegetables were the most commonly avoided. They reported that food avoidance was associated with a number of poor oral health indicators, including having dentures and fewer occlusal contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Complete natural dentition (presence of [21][22][23][24][25][26][27][28] natural teeth only -no replaced teeth present); 2. Incomplete natural dentition (presence of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] natural teeth -no replaced teeth). 3.…”
Section: Predictor and Confounding Variablesmentioning
confidence: 99%